Pemanfaatan Teknologi dan Tantangan Pembelajaran IPA di Kelas 4 SDN Plumbungan 2 - Setianingsih, Fitriana; Lutfiyatun Nisfah, Hanafi; Amelia Putri, Indah; Saputra, Marsel; Candra Puspita, Septyana; Ilham Saputra, Muhammad (Elementary School and Education Journal, 2026)
The implementation of the independent curriculum in schools currently integrates various technologies, one of which is the content of science lessons at Plumbungan 2 Elementary School Class 4. The use of technology has its own advantages and disadvantages, not only involving teachers at school, but parents are also involved in facilitating their children's needs to support the learning process. The aim of the article is to provide an overview of the use of technology in science learning in elementary schools with an independent curriculum. The methods used are observation, literature study and documentation. The results of this observation show that the use of technology in learning at SDN Plumbungan 2 Class 4, especially in science and science learning content with an independent curriculum, provides benefits in increasing student motivation and understanding of learning. On the other hand, the lack of technology and the need to increase teacher capabilities in technology are challenges in implementation. Thus, school stakeholders must be strengthened to increase the professionalism and competence of teachers at SDN Plumbungan 2 Sragen.